Cardiovascular clinical trials in Africa: opportunities and challenges - Terblanche, Marli; Burgess, Lesley (SA Heart Journal, 2017)
Africa is a continent of great diversity and consists of extremely poor and remote rural regions characterised by traditional existences, as well as highly industrialised cities populated with people following an urban westernised lifestyle. This has resulted in an interesting presentation of diseases involving the cardiovascular system. On the one hand, rheumatic heart disease, cardiomyopathy and tuberculous pericarditis remain prevalent and under-researched among the black African population, while on the other hand, cardiovascular disease and its associated risk factors are starting to emerge and currently account for 10% of all deaths. Clinical trials play a crucial role in raising public awareness and promoting good policy-making; however, the continent’s research output is still small. Opportunities and challenges facing African researchers need to be identified in order to develop a strategic plan for the way forward.